2018
DOI: 10.2147/cmar.s178567
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib in breast cancer prevention and therapy

Abstract: Breast cancer has a high incidence worldwide. The results of substantial studis reveal that inflammation plays an important role in the initiation, development, and aggressiveness of many malignancies. The use of celecoxib, a novel NSAID, is repetitively associated with the reduced risk of the occurrence and progression of a number of types of cancer, particularly breast cancer. This observation is also substantiated by various meta-analyses. Clinical trials have been implemented on integration treatment of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 141 publications
(142 reference statements)
4
43
0
5
Order By: Relevance
“…We have previously reported similar observations in colorectal cancer cells [4]. Considering that chronic inflammation is associated with an increased risk of cancer incidence and progression [65], this is a highly clinically relevant observation. COX-2, the rate-limiting enzyme in PGE 2 synthesis, is overexpressed in several cancers including BC [53,57].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We have previously reported similar observations in colorectal cancer cells [4]. Considering that chronic inflammation is associated with an increased risk of cancer incidence and progression [65], this is a highly clinically relevant observation. COX-2, the rate-limiting enzyme in PGE 2 synthesis, is overexpressed in several cancers including BC [53,57].…”
Section: Discussionsupporting
confidence: 72%
“…PGE2 stimulates tumor cell proliferation, invasion, and angiogenesis, inhibits tumor cell apoptosis, and promotes immunosuppression [54,66,67]. Preclinical and clinical studies showed that nonsteroidal anti-inflammatory drugs (NSAIDs) have chemopreventive effects on several cancers including BC [68][69][70], and exert anti-tumor activities, and in particular ketorolac when administrated in the peri-operative setting [65,71]. However, their routine use as adjuvant treatment in BC is still inconsistent and not yet recommended [72][73][74][75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of this finding with regard to the antiangiogenic effects of celecoxib in this model is limited. In view of the angiogenesis effect of the increased expression or activity of Cox-2, recently the inhibition of Cox-2 by celecoxib has been explored to be used in the treatment of diverse cancers such as breast cancer and hepatocellular carcinoma (18,53,54). So further should be performed in larger sample populations or in vitro to reveal the association between the inhibition of Cox-2 by celecoxib and angiogenesis, which may provide a more solid theoretical basis for the application of celecoxib for the treatment of adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from recent studies have suggested that NSAIDs are also capable of inhibiting angiogenesis, proliferation, the expression of aromatase P450 and epithelial-mesenchymal transition (EMT) in numerous cancer models, such as colorectal cancer, prostate cancer and human glioblastoma endothelial cells, highlighting their potentially novel properties (12)(13)(14). Additionally, the long-term use of NSAIDs has been proposed as a therapeutic Celecoxib, a selective COX-2 inhibitor, markedly reduced the severity of tamoxifen-induced adenomyosis in a murine model strategy for a number of malignancies, including prostate, colon and breast cancer (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…COX-2 suppression by Andro resulted in the inhibition of tumor growth and tumor angiogenesis in a murine breast cancer model ( Figure 2) [140]. Celecoxib is another well described specific inhibitor of COX-2, which has also been shown to inhibit IKK activity and to have anti-tumor effects in various human cancers [123,141]. Zuo and colleagues showed that celecoxib inhibits expression of NF-κB in a concentration dependent manner in pancreatic cancer cells.…”
Section: Cyclooxygenase 2 Inhibitorsmentioning
confidence: 99%